Workload, Personality and Incentives on Employee Performance - Karepesina, Nur Azizah; Zakaria, Zakaria; Labo, Irwan Adam (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study aims to assess the influence of workload, personality, and incentives on employee performance at the Jayapura City Regional Revenue Agency (Bapenda). The hypothesis is that these factors collectively significantly impact employee performance. Research Design and Methodology: The research employs a quantitative approach with a descriptive design. Data were collected through questionnaires distributed to 68 employees, selected using stratified random samples from a population of 136. The study variables include employee performance as the dependent variable and workload, personality, and incentives as the independent variables. Data analysis was conducted using multiple linear regression with SPSS version 22, including validity, reliability, and classical assumption tests to ensure the regression model's robustness. Findings and Discussion: The results indicate that the workload has a positive but insignificant effect on employee performance, while personality and incentives have a positive and significant impact. The regression model explains 68.4% of the variance in employee performance through these three independent variables. Implications: These findings suggest practical implications for Bapenda’s management in designing more effective human resource strategies by holistically considering workload, personality, and incentives. Future research should expand the scope to other government agencies and incorporate qualitative methods for deeper insights.